Sb modified Fe-Mn/TiO2 catalyst for the reduction of NO (x) with NH3 at low temperatures - Choi, Hyun; Jeong, Young Eun; Kumar, Pullur Anil; Lee, Kwan-Young; Ha, Heon Phil (SPRINGER, 2018)
Manganese-based catalysts have attracted much attention due to their excellent performance for NO reduction with NH3 (NH3-SCR) at low temperatures. In the current study, the novel metal Sb was modified into Mn/TiO2 and Fe-Mn/TiO2, and the NO (x) conversion was compared with those of Mn/TiO2 and Fe-Mn/TiO2 catalysts to investigate the effect of the Sb. The NO (x) reduction activities of the catalysts were evaluated in the temperature range of 100-250 A degrees C at a space velocity of 60,000 h(-1). The physicochemical properties of all the catalysts were characterized by Brunauer-Emmett-Teller surface area, temperature-programmed desorption of ammonia, temperature-programmed reduction, X-ray photoelectron spectroscopy, X-ray diffraction, and high-resolution transmission electron microscopy. Interestingly, the Sb-promoted Mn-based catalysts showed significantly higher NO (x) conversion than the other catalysts with or without 6 vol% of H2O. The high performance of the Sb-modified catalysts could be related to the increase of acid sites and redox properties.
Keywords: MIXED-OXIDE CATALYSTS; NITRIC-OXIDE; MODIFIED MNOX/TIO2; MANGANESE OXIDES; SCR; MN; FE; PERFORMANCE; MN/TIO2; CERIA